Benefits of air quality improvement in Klang Valley Malaysia - Rafia, Afroz; Hassan, Mohd Nasir; Awang, Muhamad; Ibrahim, Noor Akma (Inderscience Publishers, 2007)

(untitled)
The study evaluated the comparative reliability of different question formats of contingent valuation method by resurvey of the same households nine months after their original survey. The test-retest correlations are statistically significant at 1% level. Comparative reliability of different question formats has been tested comparing the test-retest correlations of these methods. This test has revealed that there is no significant difference in the test-retest correlations between the different question formats for either level A (reduction of the concentration of PM10 by 10%) or level B (reduction of the concentration of PM10 by 20%) air quality improvement.